Peace is the way : bringing war and violence to an end - Chopra, Deepak (New York Three Rivers Press, 2005)
"There is no way to peace, peace is the way." This statement has never been more true. Now, Deepak Chopra expands on A. J. Muste's insight, teaching us how to expand awareness, stop reacting out of fear, and reject war--one person at a time. As Dr. Chopra says, "Violence may be innate in human nature, but so is its opposite: love. The next stage of humanity, the leap we are poised to take, will be guided by the force of that love.""--Publisher description
War ends today -- The way of peace -- The specter of "them" -- Beyond toxic nationalism -- The myth of security -- Diabolical creativity -- The politics of the soul -- (Still) mad as hell -- Why does God want war? -- The metaphysics of terror -- The body at peace -- Our best hope.
88216
Keywords: Peace -- Religious aspects; War -- Religious aspects; Violence -- Religious aspects; Conflict management -- Religious aspects